1980
DOI: 10.1172/jci109918
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of plasma progesterone to deoxycorticosterone in men, nonpregnant and pregnant women, and adrenalectomized subjects.

Abstract: A B S T R A C T During the third trimester of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
28
1
1

Year Published

1985
1985
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 105 publications
(32 citation statements)
references
References 24 publications
2
28
1
1
Order By: Relevance
“…[l,2(N-3H]19-nor-DOC (50 Ci/mmol) was synthesized as described (12) and purified by high performance liquid chromatography (HPLC) and by gradient-elution column chromatography on celite-ethylene glycol (13). ["4CIDOC (50 mCi/mmol), purchased from New England Nuclear (Boston, MA), was purified as described (13).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…[l,2(N-3H]19-nor-DOC (50 Ci/mmol) was synthesized as described (12) and purified by high performance liquid chromatography (HPLC) and by gradient-elution column chromatography on celite-ethylene glycol (13). ["4CIDOC (50 mCi/mmol), purchased from New England Nuclear (Boston, MA), was purified as described (13).…”
Section: Methodsmentioning
confidence: 99%
“…[l,2(N-3H]19-nor-DOC (50 Ci/mmol) was synthesized as described (12) and purified by high performance liquid chromatography (HPLC) and by gradient-elution column chromatography on celite-ethylene glycol (13). ["4CIDOC (50 mCi/mmol), purchased from New England Nuclear (Boston, MA), was purified as described (13). A mixture of a tracer dose that consisted of ['4C]DOC (-18 gCi) and [3H] 19-nor-DOC (-7 uCi) in 4.5 ml NaCl (0.15 M) and 0.5 ml ethanol was infused intravenously into two healthy, ambulatory men, ages 47 and 52, and into two presumably ovulatory women, ages 33 and 35; thereafter, urine was collected from each subject for 72 h. Nonradiolabeled 19-nor-DOC was prepared as described (5) and the authenticity of this compound was validated by use of gas chromatography-mass spectrometry.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Some investigators observed in vitro, using previable fetus or fetal adrenal tissue perfused with labeled progesterone, that DOC sulfate was formed from progesterone at the adrenal gland (Bird et al, 1965;Klein etal., 1965). However, recent in vitro studies have demonstrated that steroid 21-hydroxylase and 21-hy-droxy-steroid sulfotransferase are present in extraadrenal tissues (Ottoson et al, 1984;Winkel et al, 1980;Casey et al, 1983;Casey et al, 1981). Extraadrenal production as the main site of these steroids was suggested by many authors (Pakravan et al, 1974;Dorr et al, 1986;Parker et al, 1983 b;Craig et al, 1980).…”
mentioning
confidence: 99%